Chronic pharmacological antagonism of the GM-CSF receptor in mice does not replicate the pulmonary alveolar proteinosis phenotype but does alter lung surfactant turnover. Issue 22 (26th November 2021) - Corkill, Dominic J.; Hunt, Alan N.; Hinrichs, Mary Jane; White, Nicholas; Rebelatto, Marlon; Roskos, Lorin; Nys, Josquin; Scott, Alison; Robinson, Matthew J.; Ryan, Patricia; Postle, Anthony D.; Sleeman, Matthew A.
Abstract: Granulocyte macrophage colony stimulating factor (GM-CSF) is a key participant in, and a clinical target for, the treatment of inflammatory diseases including rheumatoid arthritis (RA). Therapeutic inhibition of GM-CSF signalling using monoclonal antibodies to the α-subunit of the GM-CSF receptor (GMCSFRα) has shown clear benefit in patients with RA, giant cell arteritis (GCAs) and some efficacy in severe SARS-CoV-2 infection. However, GM-CSF autoantibodies are associated with the development of pulmonary alveolar proteinosis (PAP), a rare lung disease characterised by alveolar macrophage (AM) dysfunction and the accumulation of surfactant lipids. We assessed how the anti-GMCSFRα approach might impact surfactant turnover in the airway. Female C57BL/6J mice received a mouse-GMCSFRα blocking antibody (CAM-3003) twice per week for up to 24 weeks. A parallel, comparator cohort of the mouse PAP model, GM-CSF receptor β subunit (GMCSFRβ) knock-out (KO), was maintained up to 16 weeks. We assessed lung tissue histopathology alongside lung phosphatidylcholine (PC) metabolism using stable isotope lipidomics. GMCSFRβ KO mice reproduced the histopathological and biochemical features of PAP, accumulating surfactant PC in both broncho-alveolar lavage fluid (BALF) and lavaged lung tissue. The incorporation pattern of methyl -D9 -choline showed impaired catabolism and not enhanced synthesis. In contrast, chronic supra-pharmacological CAM-3003 exposure (100 mg/kg) over 24 weeks did not elicit a histopathological PAP phenotype despite some changes in lung PC catabolism. Lack of significant impairment of AM catabolic function supports clinical observations that therapeutic antibodies to this pathway have not been associated with PAP in clinical trials.